Determination of plant-available manganese in Finnish soils - Mäntylahti, Väinö (Agricultural and Food Science, 1981)
The aim of the study was to determine the plant-available manganese in the soil and to study which factors regulate the plant-available manganese. The material consisted of 193 mineral soils and 17 organogenic soils. Oats (Avena saliva L.), Italian ryegrass (Lolium multiflorum Lam.) and turnip rape (Brassica campestris oleifera L.) were used as the test plants in the pot experiments. A cation exchange resin method was developed for extracting soil manganese. The method enabled both exchangeable and reducible manganese to be determined. Exchangeable manganese comprised the manganese which was freely present in the soil solution in cationic form, and the manganese in cationic form which could be exchanged from the soil. Reducible manganese was the manganese reducible to the oxidation state, Mn2+, by the action of hydroquinone, hydroxylammonium chloride or ascorbic acid. The content of exchangeable manganese in the soil explained 33,7 % of the variation in the manganese content of the first yield of ryegrass. The greater the number of yields harvested, the smaller was the significance of the content of exchangeable manganese in the soil as an independent variable. On the other hand, when the content of reducible manganese in the soil was used as the independent variable, then the greater the number of yields harvested, the better it explained the variation in the manganese content of the yield. The content of manganese reduced by hydroxylammonium chloride explained 68,6 % of the variation in the manganese content of the fourth yield. The contents of exchangeable manganese and manganese reducible by ascorbic acid explained 73,4 % of the variation in the manganese content of the roots. The pH, the organic carbon content and the content of hydroquinone-reducible manganese in the soil explained 67,0 % of the variation in the content of exchangeable manganese in the plough layer of the mineral soils. The content of "total" manganese in the plough layer of the mineral soils explained 27,6 % of the variation in the content of ascorbic acid-reducible manganese. The plant stands increased the content of exchangeable manganese in the soil and decreased the redox potential of the soil in comparison to the incubated soils. The content of exchangeable manganese started to increase when the redox potential of the soil fell below 0,59 V. Adding glucose promoted the reduction of manganese in the soil, reduction appearing to be both biological and non-biological in origin. Soil moisture increased the content of exchangeable manganese when the moisture was higher than the field capacity. Liming decreased the content of exchangeable manganese in the soil more than would have been expected on the basis of the change in pH values. The manganese content and manganese uptake of the crop were also reduced. Adding large amounts of manganese (Mn 51,5 kg/ha*20 cm) did not prevent liming (calcite 14 t/ha*20cm) from reducing the manganese content of the yield.